Pro Kontra Presidential Threshold Sebagai Persyaratan Pencalonan Presiden Pada Pemilu 2019 (Jurnal Nawala Politika, 2023)
In the presidential election system in Indonesia, there is a concept of threshold or Presidential Threshold which regulates the minimum amount of support needed to nominate a presidential candidate. The law stipulates that political parties must propose pairs of such candidates. There are several arguments often presented by critics against the application of thresholds in presidential elections, both for and against. The application of this threshold has an impact on political parties. The research method used in this study is qualitative research with a library research approach. The type of data used is secondary data which is then analyzed using data reduction and conclusions are drawn. The result of this study is that there are pro and con views emerging regarding this threshold. Some consider it necessary to strengthen political parties and presidential systems of government, while others see it as a violation of the constitutional rights of political parties. The presence of the presidential threshold has a significant impact on political parties, resulting in injustice in political contestation Keywords: Presidential Threshold, Political Party, Election